O PROTAGONISMO INFANTIL POR MEIO DA RESISTÊNCIA EM KAMCHATKA (2003) - Santiago oliveira, Keyla Andrea; Ribeiro, Pollyanna Rosa (COLLOQUIUM HUMANARUM, 2020)
Our assumption is that cinema and its aesthetic devices can reveal subtleties that the daily life so often does not allow us: the child's look on the world and its inherent dramas of childhood. And what can we access about childish afflictions in the face of social control governed by the centralization of power in the military and by the loss of rights? The proposal of this work is to develop a discussion about the reading of the child in a vulnerable social context through the Argentinean film Kamchatka (2003). It shows the power of child resistance. It is from the perspective of the 10-year-old protagonist, Matías (Harry), who accompanies the confluence of tension, playfulness and also the enigma of resistance that parents experience before the dictatorship. This article is linked to the research .,it has as a research methodology the filmic analysis and takes as theoretical reference Adorno and Horkheimer (1985), Adorno (1992), Bernadet (1985), Bordwell (2013), Gardies, Rojas (2014), Truffaut (2005). The results point to the vigor of the filmic work by unveiling the impact of the imperative penetration of barbarism of the dictatorship in the various social intricacies, especially in children lives. Nuestra presuposición es que el cine y sus dispositivos estéticos pueden revelar sutilezas que lo cotidiano tan inmediatista muchas veces no nos permite: la mirada del niño sobre el mundo y sus dramas inherentes a la infancia. ¿Y qué podemos acceder sobre las aflicciones infantiles ante el control social regido por la centralización del poder en los militares y por la pérdida de los derechos? La propuesta de este trabajo es emprender una discusión sobre la lectura del niño en un contexto social vulnerable a través de la película argentina Kamchatka (2003) y su potencia como ser de resistencia. Es bajo la óptica del protagonista de 10 años de edad, Matías (Harry), que acompañamos la confluencia de la tensión, de la ludicidad y también del enigma de la resistencia que los padres experimentan ante la dictadura. ...